1998
DOI: 10.1038/sj.bjp.0701652
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of transcription factor NF‐κB by enantiomers of the nonsteroidal drug ibuprofen

Abstract: 1 The nonsteroidal drug ibuprofen exists as an R(7)-and S(+)-enantiomer. Only the S(+)-enantiomer is an e ective cyclo-oxygenase inhibitor, while the R(7)-enantiomer is inactive in this respect. Thus the molecular mechanism by which R(7)-ibuprofen exerts its anti-in¯ammatory and antinociceptive e ects remains unknown. 2 In this study the e ects of the enantiomers of ibuprofen on modulation of transcription factors have been examined with electrophoretic mobility-shift assay (EMSA), transient transfection exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
1
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(57 citation statements)
references
References 51 publications
(67 reference statements)
3
51
1
2
Order By: Relevance
“…One known COX-independent activity of both R-ibuprofen and R-flurbiprofen in the same range of Ab42 reduction dosage is NF-jB inhibition (Scheuren et al 1998;Tegeder et al 2001a) and NF-jB has been reported to selectively induce Ab42 production (Tomita et al 2000). Therefore, we tested the Ab42 lowering activity of a specific NF-jB inhibitor (SN-50) at doses which effectively inhibit translocation of the NF-jB active complex into the nucleus (Lin et al 1995).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One known COX-independent activity of both R-ibuprofen and R-flurbiprofen in the same range of Ab42 reduction dosage is NF-jB inhibition (Scheuren et al 1998;Tegeder et al 2001a) and NF-jB has been reported to selectively induce Ab42 production (Tomita et al 2000). Therefore, we tested the Ab42 lowering activity of a specific NF-jB inhibitor (SN-50) at doses which effectively inhibit translocation of the NF-jB active complex into the nucleus (Lin et al 1995).…”
Section: Resultsmentioning
confidence: 99%
“…High doses of ibuprofen and both S-and R-enantiomers inhibit NF-jB (Scheuren et al 1998;Tegeder et al 2001a) and NF-jB has been reported to specifically induce Ab42 production (Tomita et al 2000). Therefore, we tested the ability of an NF-jB peptide inhibitor to inhibit Ab42 production.…”
mentioning
confidence: 99%
“…The significance of results when compared with the TNF-treated cells are *P>0.1, **Po0.1, ***Po0.01, ****Po0.001 Downregulation of NF-jB, COX-2, cyclin D1, and proliferation by NSAID Y Takada et al Bryant et al, 2003). Scheuren et al (1998) showed that R(À)-ibuprofen as well as the S( þ )-enantiomer inhibited the activation of NF-kB in response to T-cell stimulation. One recent report showed that low doses of celecoxib inhibit IL-1-induced NF-kB activation and high doses stimulate it (Niederberger et al, 2001), whereas in our system, celecoxib alone did not activate NF-kB.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, both antiproliferative and anti-inflammatory effects of NSAID can be explained through their ability to suppress NF-kB. Although aspirin was the first NSAID shown to suppress NF-kB (Kopp and Ghosh, 1994), now several NSAID have been shown to suppress NF-kB activation (Kazmi et al, 1995;Scheuren et al, 1998;Yamamoto et al, 1999;Chuang et al, 2002;Bryant et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Adenovirus-mediated overexpression of IB␣ and liposome-mediated transfection with decoy oligonucleotides in a CF airway epithelial cell line has been shown to decrease TNF␣-induced IL-8 secretion and NFB activity (50). In addition, the nonsteroidal anti-inflammatory drug ibuprofen has been shown to inhibit NFB activity, thereby preventing the expression of inflammatory cytokines (51)(52)(53). These studies have yielded promising results that suggest that NFB may indeed be a key target for development of anti-inflammatory therapeutics for CF.…”
Section: Myd88⌬ Inhibits Ne-induced Irak Degradation and Il-8 Reportementioning
confidence: 99%